Draft Sixth Five Year Plan, 1980-85 and Annual Plan 1981-82 Volume-II Government of West Bengal - Planning Commission (Planning Commission, 1980)
Head of Development Outlays and Expenditure Development Schemes/ Projects Outlays and Expenditure Heads of Development Draft Sixth Five Year Plan, 1980-85 and Annual Plan, 1991-82 Draft Sixth Five Year Plan, 1980-85 and Annual Plan 1981-82. Targets of Production and Physical Achievements 232 Draft Sixth Five Year Plan, 1980-85 and Annual Plan 1981-82. Development Schemes/Projects -Outlays and Expenditure Draft Sixth Five Year Plan, 1980-85 & Annual Plan, 1981-82 - R. M. N. P. Outlay and Expenditure Draft Sixth Five Year Plan,1980-85 & Annual Plan, 1981-82 - Targets & Physical Achievements Physical Programmes - R. M. N. P. Annual Plan - 1981-82 Centrally Sponsored Schemes Outlays Draft Sixth Five Year Plan, 1980-85 and Annual Plan 1981-82. State Plan Outlays Under Tribal Sub-Plan.
Government of West Bengal, Development, and Planning Department